A Juridical Analysis of Legal Protection for Consumers Regarding Losses in TikTok Shop Transactions Based on Law Number 8 of 1999 concerning Consumer Protection: Kajian Yuridis Terhadap Perlindungan Hukum Bagi Konsumen Atas Kerugian Dalam Transaksi Tiktok Shop Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Michellia Alba; Mohamad Tohari; Idul Hanzah Alid (Journal of Creative Power and Ambition (JCPA), 2026)
The emergence of social commerce platforms such as TikTok Shop has streamlined the buying and selling process, yet this convenience has simultaneously opened new avenues for consumer harm arising from information asymmetry and dishonest trading practices. This paper sets out to examine how legal protection for TikTok Shop consumers is actually carried out on the ground, what obstacles hinder it, and what remedies might be pursued, grounded in Law Number 8 of 1999 concerning Consumer Protection (UUPK). An empirical juridical method is applied, with data gathered directly through interviews with sellers, delivery couriers, and consumers who experienced losses, supplemented by field observation and literature review. Findings show that legal protection has not functioned as intended, owing partly to regulatory voids, sellers' and platforms' self-limited liability, and recurring patterns of fraud together with unilateral order cancellations by sellers. The study further identifies friction between the UUPK and other digital-law instruments, leaving consumers in a state of legal uncertainty. Ultimately, conventional legal frameworks appear insufficiently agile to keep pace with today's digital trade landscape, pointing to a need for regulatory alignment, more assertive state oversight, and consumer legal education to genuinely safeguard basic rights.